Genocide and resistance Nr. 35(1) - Buchaveckas, Stanislovas; Stravinskienė , Vitalija; Veilentienė, Audronė; Burinskaitė, Kristina; Ivanauskas , Vilius; Arlauskaitė-Zakšauskienė , Inga (Genocidas ir rezistencija, 2014)
Full Issue